Eksistensi Pendidikan Kewarganegaraan di Perguruan Tinggi Dalam Memperkokoh karakter Bangsa Indonesia - Pahlevi, Farida Sekti (Ibriez : Jurnal Kependidikan Dasar Islam Berbasis Sains, 2017)
Citizenship education is an integral part of the national education system.Therefore the civic education process needs to be addressed in the curriculum and learning on all paths and levels of education.Functions and roles in the context of achieving national educational objectives, civic education are designed, developed, implemented and evaluated in the context of the embodiment of national education objectives.They are the foundation and frame of mind for understanding and applying civic education.Citizenship education is a very urgent need for the nation in building a safe, comfortable, peaceful, prosperous life.In building a civilized democracy, it needs a generation of intelligent, strong-minded nation.There are several reasons why civic education is urgently needed, firstly, the rise in political literacy and not political literacy and not knowing the workings of democracy and its institutions;Secondly, the increased politichal apathism is demonstrated by the lack of citizen involvement in political processes.The intellectual, emotional, social, and spiritual formation of intelligent citizens is really a demand and necessity.This is where the existence of civic education becomes a very important tool for democratic countries including the state of Indonesia in order to give birth to a generation of nations who know the values of nationality based on Pancasila and have the necessary skills in transforming, actualizing and preserving everything that is owned by NKRI.